In-situ construction of magnetic raspberry-like ZnO/C supporting different transition metal (Fe, Co, Ni) species with high adsorption-photocatalysis efficiency. (1st April 2023) - Jiang, Qiushi; Yu, Hailing; Zhao, Chunli; Han, Zhaolian; Li, Jiapeng; Zhang, Jingjing; Cheng, Zhiqiang
Abstract: Organic pollutants that are difficult to degrade with potential biological toxicity are challenges in the environmental field. Magnetic raspberry microspheres of three transition metal (Fe, Co, Ni) nitrate sources were prepared by simple chemical route using zinc gluconate aqueous solution as precursor, the adsorption-catalytic efficiency of which was studied in detail. The effects of the types of transition metal sources, zinc sources, carbon sources and addition amount on the phase composition, structure and properties were investigated. The specific surface area of the products under the optimal conditions is 531, 687 and 592 m 2 /g, which are 28, 36 and 31 times higher than that of the products with glucose porous carbon alone. In addition, the products also show excellent photoelectric, paramagnetic properties and stability. Interestingly, the phase compositions are Fe/ZnO/ZnFe2 O4, Co/ZnO and ZnO/Ni3 ZnC0.7 coated with carbon substrate, quite different when the same amount of Fe, Co and Ni nitrates introduced into hydrothermal system, demonstrating heterojunction/doping, doping and heterojunction effects, respectively. Within 40 min, the microspheres could rapidly remove 65.6 mg/g, 146.1 mg/g and 114.6 mg/g of Rhodamine B, respectively, higher than the adsorption of glucose carbon (18.8 mg/g), of which the adsorption processes were in accordance with Pseudo second kinetics and Langmuir monolayer adsorption. These findings not only provide a strategy for the construction of magnetic raspberry microspheres ZnO/C composites with transition metal nitrate salts, but also contribute to the analysis of adsorption-photocatalysis mechanism, which has practical application in the environmental field. Graphical abstract: Image 1 Highlights: Effect of Zn, Fe and Co sources on raspberry-like ZnO/C species were studied. Proved to possess paramagnetism, high specific area and charge transfer capability. Excellent adsorption-catalytic and regeneration effects compared with carbon spheres. RhB removal capacity could reach 146.1 mg/g with the removal rate being 97.7%.